Neoconservadorismo no blog Escreva Lola Escreva: táticas de enfrentamento ao discurso de ódio de gênero - Silva, Larissa Sousa (2022)
This research aims to advance studies on feminist coping tactics to gender hate speech on the Internet (BROWN 2018; RUEDIGER; GRASSI, 2021; SPONHOLZ, 2020). The blog Write Lola Write, object of this study, is one of the largest feminist webpages in Brazil. The blog has been active for 14 years and is authored by UFC teacher Lola Aronovich. The webpage is a space filled with debates of a political nature, and the feminist movement is a socialpolitical movement, (TELES, 1993), but it also attracts contestation and hate speech. In this study, hate speech, one of the agendas of the New Right that was formed in Brazil and Latin America (CHALOUB; LIMA; PERLATTO, 2018; SANTOS JÚNIOR, 2019; MAITINO, 2018) is theorized as a strategy (SPONHOLZ, 2020) of the new gender conservatism (BIROLI; MACHADO; VAGGIONE, 2020), with highlight to the features in the online environment. Comments posted in the time frame of the 2018 presidential elections (October 7-28) were selected. Through Content Analysis (SAMPAIO; LYCARIÃO, 2018) the diversity of attacks against feminisms (how it appears and to whom it is addressed) is mapped. Then, the reaction to this discursive flow of hatred is analyzed through Content Analysis and through a semi-structured interview (MANZINI, 2004) with Lola. The mapping of hate speech in Write Lola Write showed that it presents itself mainly in the attack on the staves of the left and in the attack on Lola. There was also an attempt to attack the commentators, but hate content has found blocking filters (coping) when sending the messages (moderation). Still, Lola allows the publication of hate speech as a strategy to show the public that that content exists and also for the purpose of personal protection, opting for archiving threats as evidence for justice.